The Need for Strengthening Health Information Dissemination Toward Indoor Residual Spraying for Malaria Prevention in Malarious Area of Ethiopia - Mekasha, Wubayehu; Daba, Chala; Malede, Asmamaw; Debela, Sisay Abebe; Gebrehiwot, Mesfin (Frontiers in Public Health, 2022)
Introduction: Malaria remains prevalent in developing countries. This is particularly true among the community who are prone but do not apply malaria prevention and controlling strategies. In one of the malarious area of Ethiopia (Shewa Robit), the acceptance level of indoor residual spraying (IRS) is indicated to be low as per guidelines. However, factors determining communities’ acceptance of IRS are not well investigated. Hence, this study was designed to identify determinants for the acceptance of IRS in order to indicate priorities for malaria prevention and control. Methods: A community-based cross-sectional study design was used among 649 households in Shewa Robit town, from February to March 2021. Households were selected from five IRS targeted kebeles. Data was collected using structured questionnaire. A multivariable logistic regression model was used to identify the independent factors associated with the acceptance of IRS. Results: The response rate in this study was 98%. The proportion of community who accepted IRS for malaria prevention was 56.5 % (95% CI: 52.7%-60.2%). Being male (AOR= 2.21, 95% CI: 1.32-3.72), having good knowledge (AOR=2.25, 95%CI: 1.33- 3.84), did not paint/re-plaster the wall after spraying [AOR= 3.99, 95% CI: 2.36-6.76), did not perceive any side effects after spraying (AOR= 1.82, 95% CI: 1.11- 2.99), effectiveness of previous IRS (AOR:2.99, 95% CI: 1.85-4.84), non-utilization of Long Lasting Insecticide Treated Net (LLIN) (AOR: 0.52, 95% CI: 0.33- 0.84), and spraying the house at the right season (AOR: 2.14, 95%CI: 1.11-4.13) were determinant factors for the acceptance of IRS. Conclusions To increase the acceptance level of IRS among the communities, health interventions and services should focus on awareness creation towards the effectiveness of IRS, proper spraying time/season, and side effect of IRS. Therefore, strengthening health services information dissemination could help promote the wise use of IRS and enhance its acceptance at the community level.